Chemical constituents and coagulation activity of Agastache rugosa. Issue 1 (December 2017) - Cao, Pengran; Xie, Pingyao; Wang, Xuebiao; Wang, Jinmei; Wei, Jinfeng; Kang, Wen-yi
Abstract Background In the Chinese traditional medicine, plant ofAgastache rugosa (Fisch. & C.A. Mey.) Kuntze (A. rugosa ) has been used to treat nausea, vomiting and dispel damp. However, currently, few reports about the chemical constituents, especially the non-volatile components ofA. rugosa are available. Methods Through separation with various column chromatographies to elucidate the chemical constituents ofA. rugosa, the biological activities of the major constituents were investigated. The extracts and main constituents ofA. rugosa were evaluated for their anticoagulant effects by assaying the activated partial thromboplastin time (APTT), prothrombin time (PT), thrombin time (TT) and fibrinogen (FIB) in vitro. Results Seven known compounds (namely compounds1 –7 ) were isolated from the aerial parts ofA. rugosa . They were identified as methyl hexadecanoate (1 ), β -sitosterol (2 ), acacetin (3 ), ursolic acid (4 ), apigenin (5 ), protocatechuic acid (6 ) and tilianin (7 ), respectively. Compounds1 and6 were isolated from the genusAgastache for the first time, and compound4 was obtained from the plants for the first time. The results showed that the extract ofA. rugosa had a significant procoagulant activity by shortening the time of PT (P  < 0.001) and increasing FIB content (P  < 0.001), as compared with Vitamin K1 . While its major constituents acacetin and tilianin exhibited significant anticoagulant activities by prolonging the times of PT, APTT, TT and reducing FIB content (P  < 0.001), as compared with blank control group. Conclusions The total extract ofA. rugosa possessed significant procoagulant activity, while its main components, acacetin and tilianin possessed significant anticoagulant activities. Further investigation should be pursued to find out the bioactivity components responsible for the procoagulant action of the plant.